The town... the house... their spirit - Robert Dulau (Institut Français de Pondichéry, 1993)
A town is not simply a collection of streets and houses with a certain number of inhabitants, but is, above all, the profound expression of the culture of the people who live in it. This book aims to provide students and teachers with analytical methods and ways of considering a town, so that they may make the place where they live their own. Pondicherry has been chosen as an example for this analysis. Various chapters deal with the site of Pondicherry, its morphology and plan, its urban landscape and landmarks, its architecture (with emphasis on the Tamil house) and its socio-cultural aspects. The book provides several drawings, maps, lists, elevations and photographs for a better reading of the town. It is available in three versions: French, English and Tamil.